Achieving hemostasis during endoscopic necrosectomy for walled‐off pancreatic necrosis using gel immersion technique. Issue 5 (22nd May 2022) - Iwano, Kosuke; Toyonaga, Haruka; Katanuma, Akio
Abstract : Watch a video of this article